Service management in IT-enabled service supply chains - Wang, Yan; Akkermans, Henk (London : SAGE Publications Ltd, 2017)
Services and information technology (IT) are dominating the current global economy. Due to the increasing involvement of IT in service operations, a new type of service supply chain (SSC) has emerged, namely the IT-enabled SSC. The present case is intended to reveal the insights of service management in such a new supply chain. Through the example of TeleSP, a northern European telecommunications and IT service provider with a complex supply chain, readers are invited to discover the unique characteristics of the IT-enabled SSC, and to view the challenges in running it.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; TeleSP; Information services industry -- European Union countries -- Case studies; Telecommunication -- European Union countries -- Case studies; Information technology -- European Union countries -- Case studies